Detection of Periodontal Pathogens from Dental Plaques of Dogs with and without Periodontal Disease - Jana Kačírová; Miriam Sondorová; Aladár Maďari; Eva Styková; Rastislav Mucha; Radomíra Nemcová; Nikola Marečáková; Jana Farbáková; Marián Maďar (Pathogens, 2022)
Dental plaque bacteria are one of the main factors responsible for the development of a periodontal disease, which is the most common infectious disease in dogs. The aim of this study was to identify the presence of periodontal disease-related bacteria in the dental plaque of dogs. Plaque samples were taken from dogs with and without periodontal disease. Samples were analyzed for the presence of Porphyromonas gulae, Tannerella forsythia and Treponema denticola using a PCR technique amplifying 16S rRNA genes of P. gulae and T. forsythia and flaB2 genes of Treponema species, including T. denticola. The presence of T. forsythia was confirmed in all samples. P. gulae was detected in all dogs with periodontal disease and in 71.43% of dogs without periodontal disease. Treponema spp. were detected in 64.29% of the samples. Based on Sanger sequencing and Basic Local Alignment Search Tool algorithm, Treponema spp. were identified as T. denticola and Treponema putidum. T. denticola was present in 28.57% of dogs with periodontal disease, while T. putidum was present in 42.86% of dogs with periodontal disease and in 57.14% of dogs without periodontal disease. T. putidum was positively correlated with both P. gulae and T. forsythia, suggesting that it may be involved in the development of periodontal disease.